(untitled) - KURNIA K, RIBKA (LATERNE, 2016)
The process of learning a foreign language, requires a source to inform one of them a textbook. Foreign language textbooks has four language skills to achieve learning objectives. Under these conditions must, as educators, to get acquainted with the practice, the suitability of the learning objectives. Textbook "Deutsch ist einfach 1" covers the four language skills, the students are taught, as not only a material, but also in the form of exercises. The problems in this research are: (1) The type of exercise the ability of writing what is included in the textbook "Deutsch ist einfach 1" for class X SMA, (2) What is the suitability of the exercise with the learning process with the textbook "Deutsch ist einfach 1" for the X SMA class. This research is descriptive qualitative descriptive analysis method. Sources of data from the textbook received "Deutsch ist einfach 1" select through exercises writing skills. The research instrument in the form of documentation guidelines checklist data. Analysis of the data by a description of the type of exercise by Bernd Kast skills and learning objectives in the textbook "German is easy 1" to write. The results of the study as follows: There are 35 practice writing skills according to the type Bernd Kast on stage preparatory exercises 8 constructive exercises exercise on stage, and five sets of exercises on stage structuring exercises. There are 11 exercises in the first half (Exercise 5, Exercise 11 Exercise 23 Exercise 24 Exercise 25 Exercise 26 Exercise 27 Exercise 28 Exercise 29 Exercise 31 Exercise 32) that does not correspond to the learning objectives 1st semester while 6 other exercises correspond to the learning objectives first half and 35 in the second half of the exercise in accordance with the purpose, the second half of the learning. Keywords: analysis, writing skills, textbook